Geological processes and orchid biogeography with applications to southeast Central America - Kirby, Stephen (Universidad de Costa Rica, 2015)
This contribution owes its origins to a paper and presentation by Dr. Calloway H. Dodson at the Second International Conference on Neotropical Orchidology held in San José, Costa Rica in May of 2003 (Dodson 2003). Dr. Dodson outlined some of the reasons to suspect that regional geological fac- tors may play important roles in orchid speciation and biogeography and gave examples from the northwestern South America. He also suggested that evolutionary change in orchid might occur over fair- ly short time periods, perhaps even as short as decades, centuries or millennia (Dodson 2003, SHK lecture notes).